IMPLICATIONS OF GOVERNMENT LEGAL SUBJECT STATUS AS ONE OF THE CAUSES OF TAX DISPUTES ON PRODUCTION SHARING CONTRACTS FOR THE OIL AND GAS INDUSTRY IN INDONESIA - Mulyo Basuki (Faculty of Law, Universitas Sebelas Maret, 2020)
Supreme Court Decision Number 2424/B/PK/Pjk/2020 states that the PSC (Production Sharing Contract) is a Government to Business (